Chip club: Japanese consortium proposes milestone microprocessor. - Thornton, Emily (Far Eastern Economic Review, 1997)
In late January 1997, Japan's largest companies organized a consortium with several research labs and South Korea's Samsung Electronics to produce a new architecture for semiconductor chips. If realized, the design could give rise to a new generation of microprocessors and could give the consortium's members a place at the high end of the semiconductor industry. The consortium intends to examine a proposal to merge the computer's memory and microprocessor—presently two different chips—on one slab of silicon. Japanese and South Korean firms have good reason to hope that the consortium will be successful in building the chip, called parallel processing RAM (random access memory), or PPRAM, because it would fulfill their ambition to produce their own microprocessors.